Secular State, NKRI Bersyariah, and NU’s Civilization Fiqh: Navigating the Dynamics of Sharia-State Relations and the Role of Political Parties in Indonesia - Riwanda, Agus; Ulath, Sanusi (ADDIN, 2024)
The debate over Sharia implementation in democratic countries remains a persistent issue, driven by political, economic, and social challenges that fuel the demand for alternative governance systems. This study examines the discourse through the perspectives of Abdullahi Ahmed An-Na’im, the concept of NKRI Bersyariah (Sharia-based Indonesia), and the Nahdlatul Ulama (NU) Civilization Fiqh. Using a library research method, primary and secondary sources were analyzed comparatively to identify key themes and concepts. An-Na’im advocates for a secular state that upholds pluralism and individual freedom, arguing that Sharia should not automatically serve as the basis for state law but must evolve within diverse social and political contexts. In contrast, NKRI Bersyariah is justified through arguments of alignment between Sharia and Pancasila, Indonesia’s Muslim majority, its utility in reducing crime and state expenses, and its role in safeguarding against extreme ideologies. NU’s Civilization Fiqh integrates Sharia with human rights, emphasizing contextually relevant Islamic laws while rejecting the formalization of Sharia as state law to maintain Indonesia’s pluralistic identity. Islamic political parties, including PKB, PKS, and PAN, adopt different approaches to the implementation of Islamic Sharia through legislation, prioritizing electoral gains while navigating Indonesia’s democratic principles, reflecting the complexities of reconciling religious values with a pluralistic and democratic society.